Peningkatan Kompetensi Front End Web Programming: Pelatihan Bahasa Pemrograman HTML dan CSS bagi Mahasiswa - M. Miftach Fakhri; Muhammad Fardan; Muhammad Alif Leo; Wulandari Wulandari; Muh. Dadang Hawari (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2023)
This program proposes and evaluates the implementation of a training programme titled "Improving Students' Front-End Competencies by focusing on HTML and CSS" to prepare students' web programming competencies. A preliminary study was conducted to analyse students' initial HTML and CSS competency levels which will provide the basis for designing an appropriate training programme. The implementation of the programme was carried out in accordance with the plan and schedule that had been set. Evaluation was conducted through monitoring participants' participation and their responses during the socialisation activities.  The results of this study are expected to provide insight into the effectiveness of a programme to improve HTML and CSS skills in building front end websites. The conclusion of this research can provide a basis for the development of students' web programming front end competence in HTML and CSS.